Freedom of expression on everyone's lips Interview with Dr. Betzabé Marciani - Loaiza Tapia, José Sebastián (2017)
The present interview seeks for giving answers to some questions referred to the freedom of speech and some of the emerging challenges of these days. The interviewed give us her informed opinion referred to the reach, the limits and the content for freedom of speech in some particular situations where this freedom is put into challenge, mainly in context of demand of tolerance and cultural diversity.